The Dark Side of Melanin Secretion in Cutaneous Melanoma Aggressiveness - Cabaço, Luís C.; Tomás, Ana; Pojo, Marta; Barral, Duarte C. (Frontiers in Oncology, 2022)
Skin cancers are among the most common cancers worldwide and are increasingly prevalent. Cutaneous melanoma (CM) is characterized by the malignant transformation of melanocytes in the epidermis. Although CM shows lower incidence than other skin cancers, it is the most aggressive and responsible for the vast majority of skin cancer-related deaths. Indeed, 75% of patients present with invasive or metastatic tumors, even after surgical excision. In CM, the photoprotective pigment melanin, which is produced by melanocytes, plays a central role in the pathology of this disease. Melanin absorbs ultraviolet radiation and scavenges reactive oxygen/nitrogen species (ROS/RNS) resulting from the radiation exposure. However, the scavenged ROS/RNS modify melanin and lead to the induction of signature DNA damage in CM cells, namely cyclobutane pyrimidine dimers, which are known to promote CM immortalization and carcinogenesis. Despite triggering the malignant transformation of melanocytes and promoting initial tumor growth, the presence of melanin inside CM cells is described to negatively regulate their invasiveness by increasing cell stiffness and reducing elasticity. Emerging evidence also indicates that melanin secreted from CM cells is required for the immunomodulation of tumor microenvironment. Indeed, melanin transforms dermal fibroblasts in cancer-associated fibroblasts, suppresses the immune system and promotes tumor angiogenesis, thus sustaining CM progression and metastasis. Here, we review the current knowledge on the role of melanin secretion in CM aggressiveness and the molecular machinery involved, as well as the impact in tumor microenvironment and immune responses. A better understanding of this role and the molecular players involved could enable the modulation of melanin secretion to become a therapeutic strategy to impair CM invasion and metastasis and, hence, reduce the burden of CM-associated deaths.